The role of the new partnership for Africa's development in Nigeria's security dynamics - Terwase, Isaac Terungwa (2017)
The failure by the Nigerian Government to address socio-economic challenges such as unemployment, illiteracy and poverty has contributed to the security challenges posed by the Boko Haram in relation to killing of the people, kidnapping, bombing and cases of internally displaced persons. This study seeks to investigate the role played by the New Partnership for Africa's Development (NEPAD) and its partners, the Nigerian Government and other stakeholders in addressing security challenges confronting Nigeria during the Fourth Republic, particularly during the tenureship of Presidents Umaru Yar’ Adua and Goodluck Jonathan from 2009 to 2014. The objective of this study is to examine to what extent Boko Haram’s insurgency and terrorist activities affected the country’s security dynamics. It also assesses the successes and failures of the NEPAD’s plan and initiative in tackling these dynamics. This research utilizes qualitative research method, with the interview technique being the main tool for primary data collection. Six states were selected from each of the six geopolitical zones in Nigeria. The findings of this research reveal that the Northerners felt cheated and betrayed by the Southerners when the mutually agreed practice of zoning or rotational of presidency between the North and South was disregarded by the ruling People’s Democratic Party (PDP). This situation occurred when Goodluck Jonathan, a Southerner Christian, succeeded Yar’ Adua, a Northerner Muslim, as Nigerian President following the latter’s untimely death. This episode further worsened the political climate of Nigeria which was already affected by Boko Haram’s insurgency. The research also shows that NEPAD’s close partnership with the federal and state governments has led to job creation for the youths. This study would contribute to the body of knowledge based on the theoretical perspective of integration theory on the strengthening of peaceful coexistence of the people through national integration. The study would assist the policy makers in the field of peace and security to emulate Nigeria, especially countries that may be confronting with similar challenges.